Efforts of Guidance and Counseling Teachers in Overcoming Cases of Bullying in Schools - Yulianti, Yulianti; Putri, Adinda Eka; Yolanda, Yolanda; Putra, Rian Pratama (Faculty of Education Universitas Negeri Malang, 2024)
This article was written because of the increasing cases of bullying in schools, one of the factors being the diversity of each student. Every student should respect each other's diversity so that good social relations can be established and divisions do not occur. This article was prepared with the aim of finding out what bullying is, what factors cause bullying to occur, what impacts will occur from acts of bullying, and how guidance and counseling teachers play a role in preventing bullying cases in schools.Bullying is a serious problem that has the potential to cause trauma to victims in various fields, including psychological, physical, social and academic. There are several factors that are the source of bullying which are generally classified into three aspects: family background, individual personality, and environmental influences, such as the school environment, social environment, and peers. Every individual who has experienced bullying almost always experiences similar psychological impacts. This psychological impact is a negative result that can be experienced by victims of bullying, which is clearly detrimental to themselves. The actions of the bully can have a long-term impact on the victim's psychological condition, and the victim may always remember the action, causing unpleasant memories for the victim. This impact is the most worrying thing for most people, where a person's psychological state is disturbed due to actions they don't want, and the perpetrator becomes a figure who is feared by many people.Guidance and counseling teachers or counselors have a central role in preventing and overcoming bullying at school. Therefore, effective and comprehensive services are needed for all students by utilizing a variety of skills and resources that can support the performance of guidance and counseling (BK) teachers. When cases of bullying occur, guidance and counseling teachers need to play an active role in resolving the problem and taking steps to prevent bullying from happening again. Guidance and guidance teachers or counselors must provide maximum and comprehensive counseling services that suit students' needs, including implementing an effective counseling guidance program to overcome bullying problems at school.